Identification of potentially pathogenic bacteria from tilapia (Oreochromis niloticus) and channel catfish (Clarias batrachus) culture in Samarinda, East Kalimantan, Indonesia - ESTI HANDAYANI HARDI; RUDY AGUNG NUGROHO; GINA SAPTIANI; RIA SARINAH; MAULINA AGRIANDINI; MIRA MAWARDI (Biodiversitas Journal of Biological Diversity, 2018)
Hardi EH, Nugroho RA, Saptiani G, Sarinah R, Anggraidini M, Mawardi M. 2018. Identification of potentially pathogenic bacteria from tilapia (Oreochromis niloticus) and channel catfish (Clarias batrachus) culture in Samarinda, East Kalimantan, Indonesia. Biodiversitas 19: 480-488. This research was conducted to isolate, identify, and characterize pathogenic bacteria from feces and water of tilapia (Oreochromis niloticus) and channel catfish (Clarias batrachus) culture from two selected locations in Samarinda, East Kalimantan, Indonesia. Bacteria were cultured and isolated on NA, TSA, and BHIA media at 30oC for 24 h. Colonies of the isolated bacteria were characterized morphologically in terms of their shape, chromogenesis, edge, and size. Antibiotic sensitivity test on each bacterial isolate was completed using inhibition zone tests. Commercial antibiotics used in this research were nitrofurantoin, ciprofloxacin, oxytetracycline, chloramphenicol, nalidixic acid, gentamicin, and norfloxacin. Koch’s postulates test was done by intraperitoneal injection of bacterial suspension to tilapia (15 g weight) at 103-109 CFU mL-1 in triplicates to determine the pathogenicity of each bacterium. Overall, there were 37 isolates obtained from different sources and growth media that belonged to 14 species: Acinetobacter calcoaceticus (1 isolate), Aerococcus urinae (2 isolates), Aerococcus viridans (1 isolate), Aeromonas hydrophila (1 isolate), Citrobacter freundii (5 isolates), Enterobacter amnigenus (2 isolate), Enterobacter cloacae (4 isolates), Escherichia coli (3 isolates), Listeria sp. (1 isolate), Niseria sp. (4 isolates), Pantoea spp. (1 isolate), Pseudomonas aeruginosa (1 isolate), Staphylococcus aureus (9 isolates), and Streptococcus iniae (2 isolates). Sixteen of the isolates were grown in BHIA medium, 12 isolates in TSA medium and 9 isolates in NA medium. The highest mortality was found in tilapia injected with Enterobacter sp., Listeria sp. and Streptococcus sp. at a density of 109 CFU mL-1. However, the number of bacteria causing mortality in fish was approximately 104-108 CFU mL-1. All bacteria detected in the tilapia and channel catfish cultures were also known as putative pathogens in human.